Surgical Treatment of a Monteggia Fracture (Type I) in an Adult Dog Using Original Fixation of the Prosthesis - Mertz, Vinciane; Maitre, Pierre (VCOT Open, 2025)
The purpose of this case report is to report the outcome of a 5-year-old male American Staffordshire Terrier with a type I Monteggia lesion with a complex fracture of the ulna of the right forelimb. The dog was treated with ulnar plating and original pattern TightRope™ fixation around the ulna and plate. At 5 months postoperatively, the dog was lameness-free, with normal activity, a negative Campbell's test and a slight decrease in elbow range of motion. Successful surgical management was achieved with an acceptable functional outcome using a TightRope™ tied around the ulna and locking compression plate.
Keywords: Monteggia lesion; tightrope; dog